2020
DOI: 10.1038/s41598-020-63915-7
|View full text |Cite
|
Sign up to set email alerts
|

Sub-lattice of Jahn-Teller centers in hexaferrite crystal

Abstract: A novel type of sub-lattice of the Jahn-teller (Jt) centers was arranged in ti-doped barium hexaferrite Bafe 12 o 19. In the un-doped crystal all iron ions, sitting in five different crystallographic positions, are fe 3+ in the high-spin configuration (S = 5/2) and have a non-degenerate ground state. We show that the electron-donor ti substitution converts the ions to fe 2+ predominantly in tetrahedral coordination, resulting in doubly-degenerate states subject to the ⊗ E e problem of the JT effect. The arrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…As one alternative explanation, a sublattice of Jahn-Teller centers, if found, could in principle be connected to transport and relaxation of magnetism. Such a sublattice has been identified in Titanium-doped hexaferrite [25] with structural relaxations present in a similar temperature interval and activation energies comparable to our findings. Also, magnetic aftereffect measurements in hexaferrites provide evidence of Fe 2+ ion diffusion [8] which might influence transport via hopping between Fe 2+ sites [10].…”
Section: Discussionsupporting
confidence: 90%
“…As one alternative explanation, a sublattice of Jahn-Teller centers, if found, could in principle be connected to transport and relaxation of magnetism. Such a sublattice has been identified in Titanium-doped hexaferrite [25] with structural relaxations present in a similar temperature interval and activation energies comparable to our findings. Also, magnetic aftereffect measurements in hexaferrites provide evidence of Fe 2+ ion diffusion [8] which might influence transport via hopping between Fe 2+ sites [10].…”
Section: Discussionsupporting
confidence: 90%
“…As mentioned in Section 3, the knowledge that the distorted configurations of polyatomic systems are due to (and only to) the JTE or PJTE, is important by itself, even when they are from the third group of systems in the above classification with very large τ values. Indeed, this knowledge allows manipulating the structure and properties of such systems by means of external perturbations, targeting the JTE or PJTE parameters [23][24][25]. Such manipulations were realized in a series of two-dimensional systems with puckered or buckled out-of-plane distortions induced by the PJTE, by restoring their planar configuration with external influence [23,24], and in some hexaferrite crystals, by creating a sublattice of JTE centers via changing their oxidation state with redox dopants [25].…”
Section: Experimental Observation Of Spontaneous Symmetry Breaking the Curie Principlementioning
confidence: 99%
“…Indeed, this knowledge allows manipulating the structure and properties of such systems by means of external perturbations, targeting the JTE or PJTE parameters [23][24][25]. Such manipulations were realized in a series of two-dimensional systems with puckered or buckled out-of-plane distortions induced by the PJTE, by restoring their planar configuration with external influence [23,24], and in some hexaferrite crystals, by creating a sublattice of JTE centers via changing their oxidation state with redox dopants [25].…”
Section: Experimental Observation Of Spontaneous Symmetry Breaking the Curie Principlementioning
confidence: 99%
“…Before discussing the behavior and the origin of the soft excitation in more detail, we comment on four narrower absorption lines that are resolved at the lowest temperatures on the highfrequency wing of the excitation; they are marked by arrows in Fig. 1 20 , calculations of the adiabatic potential showed that for Fe 2+ in BaM matrix, it is the tetrahedral coordination that is most energetically favorable. We note that the intensities of the lines are higher in the x=0.2 Ba 1-x Pb x Fe 12 O 19 compound compared to the compound with x=0.1, which is in agreement with our assumption on the nature of these absorption lines due to the presence of the Pb 2+ ions.…”
Section: Thz Spectra the Soft Modementioning
confidence: 99%
“…Functional characteristics of substituted hexaferrites show an outstanding sensitivity to doping, making these materials the future candidates for novel devices of THz optoelectronics. Doped M-type hexaferrites exhibit superior magnetic characteristics, including the ferromagnetic resonance frequency located in the THz range, record values of the coercive force of up to 40 kOe 19 , and formation of a new type of Jahn-Teller sub-lattice 20 . Doping BaM with lead is expected to systematically change its dielectric properties.…”
Section: Introductionmentioning
confidence: 99%